Multidimensional Patient Profiles In Chronic Non-Specific Axial Low Back Pain - Subgrouping And Prognosis - Rabey, Martin Ian (Curtin University, 2015)
Within a chronic low back pain cohort (n=294) subgroups were derived based upon pain sensitivity, psychological factors and pain responses following repeated movements; then profiled across multiple dimensions (demographics, pain characteristics, tissue sensitivity, psychological, social, health, lifestyle, movement). Response patterns across the three subgrouping studies revealed high variability. Baseline multidimensional data, subgroups and broad intervention groupings were used to derive prognostic models for pain intensity, disability, global rating of change and bothersomeness at one-year follow-up.